Threats, Costs, and Probability of Success: Informing Conservation Choices - Butt, Nathalie; Rosner-Katz, Hanna; Binley, Allison D.; Davis, Sierra; Pon, Jade; Radu, Taylor; Bennett, Joseph (Frontiers in Ecology and Evolution, 2020)
Threat classifications allow conservationists to categorise threatening processes faced by species of conservation concern, but lack of information on threat severity hampers efforts to establish the cost-effectiveness of conservation management actions. Actions and funds are often prioritised according to the prevalence of a threat; however, probability of success of threat management is little considered. Using data from three countries, New Zealand, Australia, and the USA, we identified which threats are more prevalent, more expensive to manage, and more likely to be successfully managed. In two of the countries, New Zealand and Australia, invasive species is the most prevalent, and costly threat, and actions to address it have the lowest probability of success. Thus, prioritising actions based on prevalence rather than severity of threat may reduce efficiency. These findings provide general guidelines to agencies attempting to carry out cost effective conservation of threatened species with limited resources.